Active ageing policies in Finland - Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2004)
Ageing takes place in Finland some 15 years earlier than in other European countries. The central actors in implementing active ageing policies are ministries that have been co-operating with each other. Active ageing policy in Finland has some of the advantages of networking in a small country, and also in the anticipation of the decrease in the share of the active population. First, all three central ministries, the Ministry of Social Affairs and Health, the Ministry of Labour and the Ministry of Education co-operate with each other. The success of various ageing programmes is largely based on this. In other countries, ministries usually have independent policies. Second, social partners include representatives of employers' and employees' organisations, as the tradition of tripartite thinking is strong in Finland. Third, research organisations support the research. For example, in the Finnish Institute of Occupational Health ageing studies began as early as 1981. Fourth, active ageing policies also focus on firm-level issues in addition to measures implemented at the individual and society levels. Firms have a clear incentive to prevent pensioners on disability emerging, since firms themselves have to pay a large part of the eventual pension expenses. There are, however, also major setbacks. Active ageing programmes such as the Ageing Programme and the Well-Being at Work Programme have been implemented in Finland for a fixed time period. There is a threat that much of the networking is lost after the programmes terminate. The cooperation between ministries may also diminish in the future programmes. The major problem in Finland that is not solved by any well being programmes is that the routes to exit from work are too generous. A new work life reform to renew the values of work is also called for. Finally, the integration of worklife and family life is considered an important issue, but issues related to active non-work time are seldom considered. An example of active time use that is ignored is household work. Household work is on average one third of the labour income for men and two-thirds of the labour income for women at age 50-64. Finally, the state of senior citizen policy is not very good in Finland. Private organisations of pensioners are relatively inactive. – Retirement ; Ageing Policy ; Demographic Trends – – Väestön ikääntyminen alkaa Suomessa noin 15 vuotta aikaisemmin kuin muissa Euroopan maissa. Keskeiset toimijat ikääntymisohjelmissa ovat ministeriöt, jotka ovat toimineet yhteistyössä. Yhteistyötä on edesauttanut verkostojen luominen, mikä voi olla helpompaa pienessä maassa. Yksi esimerkki tästä on sosiaali- ja terveysministeriön, työministeriön ja opetusministeriön yhteistyö, johon eri aktiiviseen ikääntymiseen liittyvien ohjelmien onnistuminen on perustunut. Eri työmarkkinaosapuolet ovat myös osallistuneet aktiivisesti toimintaan, joka on siten perustunut pitkälle kolmikanta-ajatteluun. Tutkimuslaitokset ovat myös tukeneet tutkimusta. Esimerkkinä tästä on Työterveyslaitoksen ikääntymistutkimus, joka on saanut alkunsa jo vuonna 1981. Viimeinen tärkeä tekijä aktiiviseen ikääntymiseen tähtäävien ohjelmien onnistumiselle on yritystason toiminta. Muista maista poiketen yrityksillä on selvä kannustin välttää työkyvyttömyyttä, koska yritykset kantavat suuren osan työttömyyseläkkeiden kustannuksista. Aktiivisen ikääntymisen toimenpiteissä on kuitenkin myös omat puutteensa. Ensinnäkin ikääntymisohjelma ja työssä jaksamisen ohjelma on asetettu määräajaksi. Uhkana on, että verkosto ei jatka toimintaansa ohjelmakauden loputtua. On myös mahdollista, että ministeriöiden välinen yhteistyö ei ole riittävää tai vähenee tulevaisuudessa. Aktiivisen ikääntymisen tavoitteiden toteuttaminen edellyttää myös työmaailmaan liittyvän arvomaailman uudistamista, missä ei olla edistytty riittävästi. Yksi ongelma on myös se, että työn ja perhe-elämän yhteensovittaminen koetaan kyllä tärkeäksi, mutta kuitenkin toiminta rajoittuu yleensä työssä jaksamiseen eikä aktiivisuuteen myös työajan ulkopuolella. Yksi esimerkki ajankäytöstä, johon ei panna paljoakaan painoa, on kotitaloustyö. Kuitenkin esimerkiksi 50-64 -vuotiailla kotitaloustyön arvon on noin kolmasosa palkkatyön arvosta miehillä ja kaksi kolmasosaa palkkatyön arvosta naisilla. Voidaan myös todeta, että eläkeläisjärjestöjen aktiivisuus on varsin vähäistä.
Keywords: J26; J14; J11; 330; Flexible Altersgrenze; Altenpolitik; Arbeitsethik; Finnland; Alternde Bevölkerung